Research on the application of Fito-humate product for the potato production - Hau, Do Thi; Tri, Le Van (Academia Journal of Biology, 2014)
On the Fito-humat product application for the potato production. A field experiment had been carried out in the Gialam district, Hanoi city. The obtained data showed that the Fito-humat product played an important role in the growth and the yield of potato. The treated plants provided a leaf green color darker than in the control ones and their height was increased, too. The product concentration also created different effects on the yield of potato; although it did not increase the number of potato tubes but the enhancement of the tuber weight leaded to inrease the tuber yield to 16.5% in comparison with the control one. The highest potato tuber yield was obtained at the product concentration of 0.03-0.04%. It made a profit of 2,603,000VND/ha